2012
DOI: 10.1159/000342544
|View full text |Cite
|
Sign up to set email alerts
|

Two New de novo Interstitial Duplications Covering 2p14–p22.1: Clinical and Molecular Analysis

Abstract: We provide a detailed clinical and molecular analysis of 2 patients with de novo interstitial duplications at 2p14–p16.1 and 2p16.1–p22.1. The 10.13-Mb duplication of chromosome 2p14–p16.1 was identified in a 9-year-old boy with mental retardation, behavioral problems (hyperactivity, hyperphagia, and subsequent vomiting), recurrent respiratory tract infections, macrocephaly, epilepsy, and dysmorphic features. The 17.49-Mb duplication of 2p16.1–p22.1 was found in a 17-year-old girl with moderate mental retardat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
1
4
1
Order By: Relevance
“…The segregation of a duplication involving CNRIP1 in 20 adult patients without significant neurological or mental disorders argues against this hypothesis. The other few reports of duplications in 2p did not overlap with ours or did not indicate their precise physical positions (38)(39)(40). In another recent investigation, hypercalcaemia was described in a patient with 2p13.2-p16.1 duplication and the authors proposed it was associated with PPP3R1 duplication (41).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The segregation of a duplication involving CNRIP1 in 20 adult patients without significant neurological or mental disorders argues against this hypothesis. The other few reports of duplications in 2p did not overlap with ours or did not indicate their precise physical positions (38)(39)(40). In another recent investigation, hypercalcaemia was described in a patient with 2p13.2-p16.1 duplication and the authors proposed it was associated with PPP3R1 duplication (41).…”
Section: Discussioncontrasting
confidence: 56%
“…Some published studies have reported large duplications involving 2p14. In one study, the authors hypothesized that CNRIP1 overdose, one of the 47 genes duplicated, could be responsible for the neurological and mental disorders due to its wide expression in the central nervous system (38). The segregation of a duplication involving CNRIP1 in 20 adult patients without significant neurological or mental disorders argues against this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Cut‐out from DECIPHER v5.1 showing only cases with duplications overlapping the duplications in our patients and in the patients reported by Kasnauskiene et al [] and Guilherme et al [] ( = short stature, = no short stature, = no information about growth).…”
Section: Discussionmentioning
confidence: 85%
“…Mégarbané et al [] reviewed the literature for patients with duplication in 2p and found inconsistent phenotypes. However, breakpoints in only few patients were defined by molecular array techniques [Guilherme et al, ; Kasnauskiene et al, ]. Several authors describe growth retardation, cardiopulmonary malformations, and depending on the latter, poor life expectancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation